Scales, inequalities, and elites in Latin America - Heredia, Mariana Laura (2021)
No scholarly innovations in the study of elites have accompanied this wave of criticism. In his review of the state-of-the-art literature, Shamus Khan warns of the "faddish" nature of these debates. The first obstacle to a renewed approach to elites is the range of terms in use from diverse traditions. Elite, upper class, oligarchy, ruling class, bourgeoisie, the rich, and privileged groups are used synonymously, as if all referred to the same idea. The second obstacle is the schism between the social sciences and its methodological approaches. Social theory - especially as developed in Latin America - provides insight into the region's inequalities by emphasizing the importance of scales and exploring the ties between elites and local societies. This paper analyses different scales, types of inequality and elites in Latin America.